PEMANDUAN BAKAT DAN MINAT CABANG OLAHRAGA MELALUI METODE SPORT SEARCH PADA SISWA SMP NEGERI SE KECAMATAN KARANGANYAR KABUPATEN DEMAK TAHUN 2013/2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of the study : 1 ) To determine the student's interests against those sports , 2 ) To determine the student talent to those sports , 3 ) To determine the suitability of the results between the talents and interests of students towards those sports . Methods of data collection of this study using a questionnaire test , test talent scouting Sport Search , observation , interviews , and documentation . This study were analyzed using descriptive formula percentage .The results showed that the factors that best supports students' interest towards the sport is an intrinsic factor ( 71.83 % ) and extrinsic factors ( 61.10 % ) . Judging from the interest that each student has a 44.03 % interest in the sport of football , 25.68 % have an interest in badminton , has a 3.67% interest in the sport of martial arts , has a 5.50 % interest in the outdoor sports , has a 9.17 % interest in the sport of basketball , has a 0.91 % interest in the sport of karate , has a 8.25% interest in the sport of volleyball , has a 1.83 % interest in the sport gymnastics , and 0.91 % have an interest in the sport of table tennis . While the results of the fit between talent and interest in the sport in Secondary Schools as the District Karanganyar Demak amounted to 41.29 % are moderate